Agents of empathy: How medical interpreters bridge sociocultural gaps in genomic sequencing disclosures with Spanish-speaking families. Issue 5 (May 2019) - Gutierrez, Amanda M.; Statham, Emily E.; Robinson, Jill O.; Slashinski, Melody J.; Scollon, Sarah; Bergstrom, Katie L.; Street, Richard L.; Parsons, D. Williams; Plon, Sharon E.; McGuire, Amy L.
Highlights: Interpreters altered clinicians' language using five empathic linguistic tools. Interpreters used an average of four empathic linguistic tools per session. Contextualization and encouragement were the most frequently used linguistic tools. Use of empathic linguistic tools personalized communication of results. Use of empathic linguistic tools made language more sensitive and accessible. Abstract: Objectives: To describe how linguistic tools used by interpreters during return of genomic sequencing results may have impacted communication with Spanish-speaking families, and to discuss the implications for the role of medical interpreters. Methods: Using discourse analysis, we identified and categorized the various ways hospital-based interpreters adapted clinicians' language in 37 audio-recorded sessions in which Spanish-speaking parents participating in a clinical trial received their child's genomic sequencing results from English-speaking clinicians. Results: We found that interpreters adapted clinicians' statements using five empathic linguistic tools: contextualization, encouragement, checking comprehension, endearment, and softening. Interpreters used an average of four linguistic tools per session, with contextualization and encouragement being the most frequently used. Conclusions: Interpreters used empathic linguistic tools to alter clinicians' statements when communicating genomic information to Spanish-speaking families. Our findings demonstrate the critical role of interpreters as cultural mediators and facilitators of understanding for Spanish-speaking families. Practice implications: This study expands upon the definition of clinical empathy in interpreter-mediated sessions. Our findings suggest that revisions of standards of medical interpretation practice may be warranted regarding interpreters' ability to adapt clinicians' language in a culturally sensitive manner during interpretation.